2016
DOI: 10.1021/acs.jafc.6b00559
|View full text |Cite
|
Sign up to set email alerts
|

Antiamnesic Effect of Broccoli (Brassica oleracea var. italica) Leaves on Amyloid Beta (Aβ)1–42-Induced Learning and Memory Impairment

Abstract: To examine the antiamnesic effects of broccoli (Brassica oleracea var. italica) leaves, we performed in vitro and in vivo tests on amyloid beta (Aβ)-induced neurotoxicity. The chloroform fraction from broccoli leaves (CBL) showed a remarkable neuronal cell-protective effect and an inhibition against acetylcholinesterase (AChE). The ameliorating effect of CBL on Aβ1-42-induced learning and memory impairment was evaluated by Y-maze, passive avoidance, and Morris water maze tests. The results indicated improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…; Park et al . ). These activities are attributed to the presence of bioactive compounds such as vitamin C, carotenoids, polyphenols, glucosinolates, sulforaphane and enzymes (e.g.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Park et al . ). These activities are attributed to the presence of bioactive compounds such as vitamin C, carotenoids, polyphenols, glucosinolates, sulforaphane and enzymes (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…We suggest for first time that the inhibitory effect is probably due to AMPs. 2011;Mahn and Reyes 2012;Owis 2015;Vinha et al 2015;Park et al 2016). These activities are attributed to the presence of bioactive compounds such as vitamin C, carotenoids, polyphenols, glucosinolates, sulforaphane and enzymes (e.g.…”
mentioning
confidence: 99%
“…Furthermore, the development of senile plaques composed of extracellular accumulated β-amyloid (Aβ) peptides [2] is one of the most distinct neuropathological features of AD. It is hypothesized that Aβ peptides are toxic and contribute to memory loss, behavioral impairments, and further neurodegenerative pathology in AD [3,4]. In addition to Aβ aggregation, neuroinflammation also plays a pivotal role in the pathophysiology of AD [5].…”
Section: Introductionmentioning
confidence: 99%
“…italic. In previous study, chloroform fraction of broccoli leaf extract has been reported to ameliorate Aβ 1-42 induced learning and memory impairment, to enhance cognitive function evaluated by Y-maze, passive avoidance, and MWM tests.and inhibition against AChE [43]. It may be speculated that consumption of the broccoli may have potential for the management of dementia clinically.…”
Section: Resultsmentioning
confidence: 92%